2009
DOI: 10.1111/j.1365-2109.2009.02201.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein levels on the growth performance, digestive capacity and amino acid metabolism of juvenile Jian carp (Cyprinus carpiovar. Jian)

Abstract: This experiment was conducted to evaluate the effects of protein levels on the growth performance, digestive capacity and amino acid metabolism of juvenile Jian carp. Brown fish meal was used as the sole protein source in the present study. Six isoenergetic experimental diets containing 14.4 MJ kg−1 of digestible energy and 220–495 g crude protein kg−1 diets were fed to triplicate groups of 50 fish with a mean initial weight of 16.67 ± 0.01 g for 45 days. Per cent weight gain (PWG) and feed efficiency ratio (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 41 publications
16
39
0
2
Order By: Relevance
“…Meanwhile, Kaplan [83] reported that Na þ , K þ -ATPase carries out the uptake of Na þ in most higher eukaryotes. Studies from our laboratory showed that dietary protein supplementation could increase the activity of Na þ , K þ -ATPase in the intestines of Jian carp [84]. Thus, dietary proteins up-regulate claudin 15a (rather than claudin 15b) gene expression, which might be a feedback mechanism for increased Na þ transport capacity in the fish intestine.…”
Section: General Summary: Optimal Dietary Protein Level Improve the Imentioning
confidence: 89%
“…Meanwhile, Kaplan [83] reported that Na þ , K þ -ATPase carries out the uptake of Na þ in most higher eukaryotes. Studies from our laboratory showed that dietary protein supplementation could increase the activity of Na þ , K þ -ATPase in the intestines of Jian carp [84]. Thus, dietary proteins up-regulate claudin 15a (rather than claudin 15b) gene expression, which might be a feedback mechanism for increased Na þ transport capacity in the fish intestine.…”
Section: General Summary: Optimal Dietary Protein Level Improve the Imentioning
confidence: 89%
“…Jian. (Liu et al, 2009) but is comparable with 40% for fingerling catla Catla catla (Mohanty et al, 1990) and 41.7% for Barbodes altus (Elangovan and Shim, 1997), and lower than 45%-50% for endangered cyprinid Tor putitora (Islam and Tanaka, 2004). Protein requirements among the fish species are complicated by the difference in fish size or age, culture conditions, and nutrient interactions in experimental diets such as protein and non-protein energy levels (NRC, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…White fishmeal, soybean meal, cottonseed meal, and rapeseed meal were used as the main protein sources in all the dietary treatments. Diet 1 was formulated to contain protein level of 340.0 g/kg diet, to meet the protein requirement of juvenile Jian carp according to Liu et al (2009). Diet 2 was reduced 2% dietary protein in total by iso-proportionally reducing the amount of four protein materials based on diet 1.…”
Section: Experimental Design and Dietsmentioning
confidence: 99%